2016
DOI: 10.1161/circep.116.004432
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Impact of the Timing of Recurrence of Infarct-Related Ventricular Tachycardia After Catheter Ablation

Abstract: Background Recurrence of ventricular tachycardia (VT) after ablation in patients with previous myocardial infarction is associated with adverse prognosis. However, the impact of the timing of VT recurrence on outcomes is unclear. Methods and Results We analyzed data from a multicenter collaborative database of patients who underwent catheter ablation for infarct-related VT. Multivariable Cox regression analyses investigated the effect of the timing of VT recurrence on the composite outcome of death or heart … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 12 publications
3
9
2
Order By: Relevance
“…Our findings confirm and extend these results to a more general population of patients with scar‐related VT, including subjects with nonischemic cardiomyopathy. At variance with the findings by Siontis et al . we found a nonsignificant increase in mortality risk for VT recurrence events occurring after 6 months from the index procedure.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Our findings confirm and extend these results to a more general population of patients with scar‐related VT, including subjects with nonischemic cardiomyopathy. At variance with the findings by Siontis et al . we found a nonsignificant increase in mortality risk for VT recurrence events occurring after 6 months from the index procedure.…”
Section: Discussioncontrasting
confidence: 99%
“…Indeed, more than 50% of the death events at 2 years occurred in patients who had experienced recurrent VT within the first 6 months postprocedure with an almost sixfold increased risk of mortality. In a recently published multicenter registry including patients with infarct‐related VT undergoing VT ablation, patients with early recurrence (within 1 month) had a threefold higher risk of mortality during follow‐up, and there was a progressive decline in the subsequent mortality risk for later VT recurrences of up to 3 years after the index procedure, when the risk became comparable to patients without recurrence . Our findings confirm and extend these results to a more general population of patients with scar‐related VT, including subjects with nonischemic cardiomyopathy.…”
Section: Discussionsupporting
confidence: 85%
“…Although observational studies have demonstrated an association between recurrent VAs and mortality ( S12.1.4.12 S12.1.4.15 ), no prospective study thus far has demonstrated a significant beneficial effect of VT ablation on survival. Successful completion of a prospective trial of VT ablation with a primary outcome of mortality is challenging due to competing mortality risks in patients with VT.…”
Section: Future Directionsmentioning
confidence: 99%
“…arrythmogenic cardiomyopathy, postviral myocarditis, etc.) (Siontis et al, 2016). Despite the above, these results are a proof-of-concept that CDCs administered into the pericardial sac modify epicardial scar remodelling (both anatomically and functionally).…”
Section: Limitationsmentioning
confidence: 87%